1986
DOI: 10.1089/cns.1986.3.129
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Stimulation for the Control of Spasticity in Patients with Chronic Spinal Cord Injury: I. Clinical Observations

Abstract: The effectiveness of spinal cord stimulation for control of spasticity was studied in 59 spinal cord injury patients. SCS was markedly or moderately effective in reducing spasticity in 63% of the patients. We found that control of spasticity by SCS was not correlated with the severity of spasticity, the type of spasticity (flexor or extensor), or the ability to ambulate. However, stimulation was more effective in patients with incomplete cervical lesions than in complete cervical lesions. Stimulation below the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1
5

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 13 publications
1
49
1
5
Order By: Relevance
“…8 In an eort to clarify the precise impact of the site of stimulation, Dimitrijevic et al used SCS in a sample of 58 SCI patients and found spasticity to be more eectively controlled when the electrode was placed below, rather than above, the lesion. 9 This ®nding was again con®rmed by Barolat et al who, based on a total of 48 patients, concluded that SCS applied below the level of the lesion was an eective and safe approach to controlling SCI-related spasms. 10 The 1990s saw the interest in this approach declining, mainly due to technical problems and the realization that SCS as a method to control spasticity was less eective in patients with severe spasms of the lower limbs.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…8 In an eort to clarify the precise impact of the site of stimulation, Dimitrijevic et al used SCS in a sample of 58 SCI patients and found spasticity to be more eectively controlled when the electrode was placed below, rather than above, the lesion. 9 This ®nding was again con®rmed by Barolat et al who, based on a total of 48 patients, concluded that SCS applied below the level of the lesion was an eective and safe approach to controlling SCI-related spasms. 10 The 1990s saw the interest in this approach declining, mainly due to technical problems and the realization that SCS as a method to control spasticity was less eective in patients with severe spasms of the lower limbs.…”
Section: Introductionmentioning
confidence: 82%
“…33 It has been shown repeatedly that mild forms of spasticity can be eectively controlled by placing the electrode below the level of the spinal cord lesion. 2,5,9,10 Why this approach has failed in cases of severe spasticity becomes clear when we realize how heavily the antispastic eect of SCS depends on the site of stimulation (Figures 3 and 4). Rather than just placing the electrode below the level of the lesion, it is essential that the stimulation site targets the dorsal roots of the upper lumbar cord segment.…”
Section: Discussionmentioning
confidence: 99%
“…BMCA has been used to demonstrate the ability to modify EMG reflex excitability in many persons clinically classified as complete SCI [49]. Applications include documentation of treatment effects for returning motor control [50], assessment of spasticity and cocontraction [51], and provision of objective criteria for the selection of intervention strategies [52].…”
Section: Motor Activity Measuresmentioning
confidence: 99%
“…In patients with motor-complete and incomplete SCI, epidural SCS was applied below and above the lesion at vertebral levels ranging from C2 to T10 and at stimulation frequencies of 30-1500 Hz, with variable results. [18][19][20][21][22] Dimitrijevic et al 23,24 suggested that the diversity of physiological conditions after SCI and the placement of the epidural electrodes determined the efficacy of SCS in spasticity control. While interest in this technique declined in the 1990s, Pinter et al 25 revisited its use in individuals with chronic SCI.…”
Section: Introductionmentioning
confidence: 99%